ENVIRONMENTAL AND BIOLOGICAL CONTROLS ON ELEMENTAL (MG/CA, SR/CA AND MN/CA) RATIOS IN SHELLS OF THE KING SCALLOP PECTEN MAXIMUS - Freitas P.S.; Clarke L.J.; Kennedy H.; Richardson C.A.; Abrantes F. (My University, 2006)
The relationship between potential elemental proxies (Mg/Ca, Sr/Ca and Mn/Ca ratios) and environmental factors was investigated for the bivalve Pecten maximus in a detailed field study undertaken in the Menai Strait, Wales, U.K. An age model constructed for each shell by comparison of measured and predicted oxygen-isotope ratios allowed comparison on a calendar time scale of shell elemental data with environmental variables, as well as estimation of shell growth rates. The seasonal variation of shell Mn/Ca ratios followed a similar pattern to one previously described for dissolved Mn2+ in the Menai Strait, although further calibration work is needed to validate such a relationship. Shell Sr/Ca ratios unexpectedly were found to co-vary most significantly with calcification temperature, whilst shell Mg/Ca ratios were the next most significant control. The temporal variation in the factors that control shell Sr/Ca ratios strongly suggest the former observation most likely to be the result of a secondary influence on shell Sr/Ca ratios by kinetic effects, the latter driven by seasonal variation in shell growth rate that is in turn influenced in part by seawater temperature. P. maximus shell Mg/Ca ratio to calcification temperature relationships exhibit an inverse correlation during autumn to early spring (October to March-April) and a positive correlation from late spring through summer (May-June to September). No clear explanation is evident for the former trend, but the similarity of the records from the three shells analysed indicate that it is a real signal and not a spurious observation. These observations confirm that application of the Mg/Ca proxy in P. maximus shells remains problematic, even for seasonal or absolute temperature reconstructions. For the range of calcification temperatures of 5-19 °C, our shell Mg/Ca ratios in P. maximus are approximately one-fourth those in inorganic calcite, half those in the bivalve Pinna nobilis, twice those in the bivalve Mytilus trossulus, and four to five times higher than Mg/Ca ratios in planktonic and benthonic foraminifera. Our findings further support observations that Mg/Ca ratios in bivalve shell calcite are an unreliable temperature proxy, as well as substantial taxon- and species-specific variation in Mg incorporation into bivalves and other calcifying organisms, with profound implications for the application of this geochemical proxy to the bivalve fossil record. ? 2006 Elsevier Inc. All rights reserved.